Lessons from Korea, Switzerland and Norway: Improvement in innovation management in Iran - Seyedreza Haghi (Management Science Letters, 2013)
This article is devoted to the study of strategic issues for modification of the national innovation system of Iran. In recent years, National Innovation System is accepted as a conceptual framework and analytical instrument for countries’ innovation activities by the international organizations such as Organization for Economic Cooperation and Development, United Nations Conference on Trade and Development and Euro stat. The main purpose of this study is to find solutions modification of the national system of Iran. The subject of the research is the international experience of development of national innovation systems, peculiarities of innovation systems in countries with developed and emerging markets, as well as systems of support and management of national innovation systems in Iran and abroad. The results of this study may be useful for students, managers in public and private sector, government officials, researchers, economists and all those interested in financial and economic issues.